Thực hành quản lý trong doanh nghiệp thương mại và dịch vụ: Bằng chứng thực nghiệm ở Đồng bằng sông Cửu Long - Trịnh Công , Đức; Nguyễn Tuấn , Kiệt (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
Enterprises in the Mekong Delta area accounts for approximately 10% of Vietnam’s total enterprises. These enterprises have been operating in different economic sectors and contributing nearly 20% of the country’s GDP. However,management activities in enterprises are often neglected and not well documented. Using the new approach of Bloom and Van Reenen (2007), this paper contributes empirical evidence about quantification and explanation of management practices of businesses in trade and services sector at Mekong Delta economy. The results show that management quality of enterprises is quite poor. Management practices have a positive relationship with business productivity. Number of employees, age of enterprise, source of investment capital, human capital, level of competition, and decentralization positively affect management practices of the enterprises in the trade and services sector in Mekong Delta. In addition, the ownership factor is negatively correlated management practices.